Global Research Trends in Impulsive Buying Behavior within E-Commerce: A Bibliometric Analysis - Almashikhi, Mohammed Said; Azam, S. M. Ferdous; Khatibi, Ali (International Review of Management and Marketing, 2026)
Impulsive purchasing behavior has become a significant focus in e-commerce research owing to the swift growth of digital marketplaces and technology-fueled consuming settings. This study seeks to systematically delineate and synthesize global research trends regarding impulsive buying behavior within the realm of e-commerce using extensive bibliometric analysis. The study examines 393 peer-reviewed papers and reviews from Scopus-indexed publications between 2000 and 2025, employing recognized bibliometric methodologies such as performance analysis, citation analysis, co-authorship analysis, co-citation analysis, and keyword co-occurrence mapping. Visualization technologies like VOS viewer are utilized to elucidate the intellectual framework, thematic progression, and collaborative dynamics within the discipline. The results demonstrate a distinct historical transition from initial technology-focused study to interdisciplinary studies that incorporate consumer psychology, digital marketing, social commerce, and advanced technologies like artificial intelligence and live-stream commerce. The findings delineate key authors, institutions, nations, and journals, emphasizing the preeminent influence of the United States and China, as well as the significance of high-impact journals in information systems and consumer behavior. The thematic analysis indicates an increasing academic focus on the emotional, experiential, and social aspects of impulsive purchasing, as well as rising issues pertaining to consumer welfare and ethical platform design. This study presents a systematic assessment of the knowledge domain, identifies research deficiencies, and gives significant insights to inform future academic research, managerial decisions, and policy formulation in digital consuming situations.